Finding a home for global LNG in Europe: Understanding the complexity of access rules for EU import terminals - Katja Yafimava (The Oxford Institute for Energy Studies, 2020)
Entering the 2020s, LNG sellers are operating in an increasingly oversupplied global market, thus facing the problems of whether and where they will be able to 'find a home' for their cargoes. Given that the EU is the only liquid gas market with regulated third party access (TPA) to LNG import terminals, the sellers will always be able to place a cargo in the EU for which no other market can be accessed unless the owner/buyer agrees, and hence will need to know and understand the TPA rules for EU LNG import terminals. As no dedicated LNG-specific EU regulation exists and the Third Gas Directive and Gas Regulation 715 left a significant degree of discretion to the regulated terminal operators in respect of capacity allocation mechanisms, UIOLI procedures, and tariffs, enabling the operators to choose different ways of compliance, or apply for an exemption. This has resulted in a situation where the LNG import terminals in the EU are governed by a patchwork of terminal codes developed by their operators, the NRA guidance, and the exemptions, thus making it extremely difficult for an LNG seller to understand the rules. This paper concludes that the development of a dedicated stand-alone LNG-specific regulatory framework at the EU level, which could build on and bring together the LNG-related provisions of the Third Gas Directive and Gas Regulation 715, differing terminal codes and exemptions, would establish a level playing field and simplify the sellers' task of accessing the terminals. Further legislative initiatives on the part of the EC to amend the regulatory framework for LNG import terminals cannot be ruled out, as well as further actions by NRAs in respect of already granted (and new) exemptions. These could take the form of either developing a new LNG network code, amending the existing CAM NC (which does not apply to LNG terminals at present), and/or amending the existing exemption decisions.
Keywords: 330; access; Adriatic; auction; Barcelona; Bilbao; Capacity; Cartagena; Dragon; Dunkerque; El Musel; exempted terminals; exemption; first come first served; Fos Cavaou; Fos Tonkin; Gas Regulation 715; Gate; Grain; Huelva; Klaipeda; LNG; LNG and Storage Strategy; Montoire-de-Bretagne; Mugardos; Network Code; NG 157; NG157; OLT; open season; Panigaglia; regulated terminals; Regulation; Revithoussa; Sagunto; Sines; South Hook; Swinoujscie; Tariffs; Third Gas Directive; Zeebrugge